PERBANDINGAN HASIL BELAJAR PESERTA DIDIK MATERI INDERA PENDENGARAN MANUSIA DENGAN MENGGUNAKAN METODE SQ3R DAN SQ4R KELAS VIII DI SMP NEGERI 1 PALLANGGA KABUPATEN GOWA - Nurul Mutia Tamsil; syahruddin syahruddin; Muh Yusuf Hidayat (Jurnal Biotek, 2016)
The problems in this study were (1) How the learning outcome of students using SQ3R (Survey, Question, Read, Recite, and Review), on the sense of human auditory material in the class VIII SMP Negeri 1 Pallangga Kab. Gowa, (2) How does the learning outcome of students using SQ4R (Survey, Question, Read, Reflect, Recite, and Review), on the sense of human auditory material in the class VIII SMP Negeri 1 Pallangga Kab. Gowa, and (3) Are there differences in learning outcomes of students using SQ3R (Survey, Question, Read, Recite, and Review), and using methods SQ4R (Survey, Question, Read, Reflect, Recite, and Review) on the sense of human auditory senses material in the class VIII SMP Negeri 1 Pallangga Kab. Gowa.This study is a Quasi-Experimental Research Design with Posttest Only Control Design. In this design there are two groups and each use one of the treatment. The sampling technique used in this research is purposive sampling technique. The population in this study was all students of SMP Negeri 1 Pallangga Kab. Gowa with 325 students divided to of seven classes. The samples are class VIII6 and VIII7, each of class with 40 students. Data was collected using a test instrument with multiple choice questions of 20 questions and the observation sheet. Data analysis technique used is descriptive statistical analysis and inferential statistical analysis.The results obtained in both groups through a descriptive statistical analysis, the average results of studying biology teaching methods SQ3R (Survey, Question, Read, Recite, and Review) is 57.98 while the average result of learning biology using strategies SQ4R learning (Survey, Question, Read, Reflect, Recite, and Review) is 61.37. The results of inferential analysis data show that significant value obtained is tcount 48.42> ttable 2,000 and significance (0.000 <0.05). It can be concluded that there is a difference in learning using method SQ3R (Survey, Question, Read, Recite, and Review) and method SQ4R (Survey, Question, Read, Reflect, Ricite, and Review) to the learning outcomes of Biology in the sense of the human auditory material in the class VIII SMP Negeri 1 Pallangga Kab. Gowa.